RETRACTED: Development of an combined energy complex consisting of a micro-hydroelectric power plant and a solar photoelectric plant for the conditions of Uzbekistan - Yusupova Feruza; Sultanov Nomomjon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001